Construct Validity of the Vietnamese Version of Maslach Burnout Inventory-General Survey - Huong Thi Thu NGUYEN; Kazuyo KITAOKA; Khue Minh PHAM; Ngoc Thi Minh NGUYEN; Tran Bao NGUYEN; Huong Thi Thu PHAM; Cuong Hung NGUYEN; Linh Van PHAM; Hai Thanh PHAM (NurseLine Journal, 2021)
Back ground and Purpose: Burnout is a state of emotional, physical, and mental exhaustion caused by excessive and prolonged stress. The purpose of this study is to validate the Vietnamese version of Maslach Burnout Inventory-General Survey (MBI-GS) for burnout measuring in Vietnam. Methods: using cross-sectional study, factorial validity of MBI-GS was tested by exploratory factor analysis then accompanied by confirmatory factor analysis. Pearson’s correlation is used to check criterion-related validity. Results: the model of three factors structure without item 8 and 9 was suggested as the best fit model with chi-square (X2 = 285.13, P < .0001), root mean square error of approximation (RMSEA = 0.07), comparative fit index (CFI = 0.92), goodness of fit index (GFI = 0.91). Conclusions: The construct validity of Vietnamese version of Maslach Burnout Inventory-General Survey is acceptable for use in future investigations regarding burnout.